Calibration and performance of a real-time gamma-ray spectrometry water monitor using a LaBr3(Ce) detector. (March 2018) - Prieto, E.; Casanovas, R.; Salvadó, M.
Abstract: A scintillation gamma-ray spectrometry water monitor with a 2″ × 2″ LaBr3 (Ce) detector was characterized in this study. This monitor measures gamma-ray spectra of river water. Energy and resolution calibrations were performed experimentally, whereas the detector efficiency was determined using Monte Carlo simulations with EGS5 code system. Values of the minimum detectable activity concentrations for 131 I and 137 Cs were calculated for different integration times. As an example of the monitor performance after calibration, a radiological increment during a rainfall episode was studied. Highlights: A 2″ × 2″ LaBr3 (Ce) gamma-ray spectrometry water monitor is characterized. Experimental energy and resolution calibrations are performed. The detector efficiency is obtained by MC simulations with EGS5 code system. Minimum detectable activity concentrations for 131 I and 137 Cs are given. A rainfall radiological increment is compared with the NaI(Tl) monitor.